Regional Leading Product Development Program of Wanagiri Taro Processing Group, Sukasada District, Buleleng Regency - Luh Suriati; N K Mardewi; D K T Sukmadewi; L K Datrini; A A S Manik Cindrawati; N L P Sulis_Dewi; N P G Satria_Kesumayasa; I W Widiantara_Putra; I P A Raditya_Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Development prospects and opportunities for processed foods derived from taro have recently increased. Taro crackers are one of the snack foods that are in high demand among consumers. The Taro Processing Group of Wanagiri Village, Sukasada District, Buleleng Regency, formed in 2020 with ten members, participates in Regional Superior Product Development Programme activities. Partners have produced and marketed taro tubers processed into taro chips, but the process has not been exhaustive, and partners wish to increase the quantity and quality. As a result of their lack of knowledge in the fields of processing and effective business management, partners encounter difficulties in managing production and marketing. This activity aims to equip the Wanagiri Village Taro Processing Group with the skills and knowledge to manage local natural resources and the entrepreneurial mentality to capitalise on business opportunities related to Wanagiri Village conditions. The implementation method involves coaching, training, mentoring, and structured consultation on various partner-related issues. Regional Leading Product Development Programme Wanagiri Taro Processing Group, Sukasada District, Buleleng Regency, has yielded positive results. The Wanagiri Taro Processing Group increased its value and enhanced its living conditions. Regional Leading Product Development Programme application is possible. The community can assimilate up to 80% of knowledge regarding the processing of taro chips with varying flavours, product packaging, and marketing, which will aid in product development. In addition, comprehension exists regarding cultivating taro plants in the backyard, using taro processing waste as animal fodder, and business management. This activity should be performed continuously, along with assistance, so that the group can independently produce and sell taro snacks with various flavors.